A programmed course on respect language in modern Japanese - O'Neill, P. G. (Charles E. Tuttle, 1966)
Contents include sections on: polite and respecful words, honorific verbs, depreciatory verbs, deferntial verbs, imperative forms, and adjectives. And at the end of the work the student is offered a post-test to measure acquired ability, in addition to four invaluable appendices, providing tabulated and easily accessible information and a full index of items.